MODERATION OF RELIGIOUS CONTROL ON AUDITORS' DYSFUNCTIONAL BEHAVIOR - Radhiyah, Hana Rihab; Basri, Yesi Mutia; Rusli, Rusli (Jurnal Al-Iqtishad, 2024)
This study aims to analyze the effect of locus of control, professional commitment, and self-esteem on dysfunctional audit behavior and analyze the effect of locus of control, professional commitment and self-esteem on dysfunctional audit behavior moderated by religious control. The residents in this study are auditors in the Pekanbaru, Padang, Batam, and Jambi areas. The sample in this study was 84 respondents. The data analysis technique used in this study is Structural Equation Modeling (SEM) using the Partial Least Square (PLS) application. Based on the results of research, internal and external locus of control and professional commitment have no effect on dysfunctional audit behavior. Self-esteem is proven to have a significant effect on dysfunctional audit behavior. Religious control as a moderating variable is able to moderate the relationship between external locus of control on dysfunctional audit behavior but cannot moderate the relationship between internal locus of control, professional commitment, and self-esteem on dysfunctional audit behavior. The results of this study confirm that several factors can cause dysfunctional audit behavior to occur, and therefore auditing organizations (IAPI) should include training for their auditors regarding this.